Impact of tiered pricing reform on China's residential electricity use - Min Wang; Xiumei Yu (China Economic Quarterly International, 2021)
Based on a county-level monthly panel data from four provinces and a province-level monthly panel data from 21 provinces from 2009 to 2015, we use the regression discontinuity method to examine the impacts of the tired pricing reform implemented in July 2012 on residential electricity use in China. The county-level (province-level) estimation shows that the tiered pricing reform has reduced the monthly electricity use per household by 6.5 ​kWh (8.9 ​kWh), accounting for 6.1% (7.1%) of the monthly electricity use per household. Moreover, counties and provinces with a more drastic policy shift have shown a larger decrease in residential electricity use.